Why Do We “Like” on WeChat Moments: The Effects of Personality Traits and Content Characteristics - Zheng, Chun; Song, Xingyu; Li, Jieyun; Chen, Yijiang; Dong, Tingyue; Yang, Sha (Frontiers in Psychology, 2022)
To probe the motivational roles of hedonic gratification and social gratification in giving “Like” feedback on social media, we developed a set of novel pictures to simulate WeChat Moments. We subsequently examined how the personality trait of extraversion and stimulus content characteristics (e.g., emotional valence, personal relevance) influenced “Liking” behavior. A 2 (extraversion: extrovert group vs. introvert group) × 3 (emotional valence: positive vs. neutral vs. negative) × 2 (personal relevance: personally relevant vs. personally irrelevant)-mixed experimental design was applied to data obtained from 56 WeChat Moments users. These participants included 28 individuals with the highest extraversion scale scores (the extrovert group), and 28 individuals with the lowest extraversion scale scores (the introvert group), according to the NEO Five-Factor Inventory. Briefly, participants observed pictures on an interface similar to that of WeChat Moments and were given the option to “Like” each picture. “Like” rates and response time were then compared across groups and conditions by applying a mixed-design analysis of variance. Pearson's correlation coefficients were calculated to explore relationships between the “Like” rates under each condition and the scores for each personality trait. Compared with the neutral pictures, the positive and negative pictures were “Liked” more and less frequently, respectively (F_2,108=46.22,p<0.001). Compared with the poster-unrelated pictures, the personally related pictures were “Liked” more frequently (F_1,54=19.54,p<0.001). In the extrovert group, the frequency of “Likes” given to unrelated negative content positively associated with neuroticism (r=0.42,p=0.025) and negatively associated with conscientiousness (r=-0.46,p=0.014). No correlations were observed in the introvert group. Compared with not giving “Like” feedback, participants gave “Likes” to positive and negative pictures more quickly (p=0.035) and slowly (p<0.001), respectively. These results support the hypothesis that hedonic gratification and social gratification motivate “Like” feedback for positive content and personally related content, respectively. “Liking” behavior was not affected by extraversion, but was related to neuroticism and conscientiousness. Content-related differences in time intervals for giving “Like” feedback in this study suggest that people do not hesitate to give “Like” feedback to positive content on WeChat Moments, yet linger in deciding to give “Like” feedback to negative content.